2022
DOI: 10.1213/ane.0000000000006036
|View full text |Cite
|
Sign up to set email alerts
|

Relationships Between Body Mass Index, Allogeneic Transfusion, and Surgical Site Infection After Knee and Hip Arthroplasty Surgery

Abstract: BACKGROUND: Increased body mass index (BMI) is considered as an important factor that affects the need for total knee and hip arthroplasty (TKA/THA) and the rate of perioperative complications. Previous investigations have not fully established the relationship of BMI and perioperative transfusion with surgical site infection (SSI) or the relationship of BMI and perioperative transfusion after TKA or THA. METHODS: The National Surgical Quality Improvement Program database was used to perform a retrospective co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 31 publications
1
5
0
Order By: Relevance
“…Baykara et al argue an absence of any significant differences in the functionality between standard GC and purified GC after more than 24 h of storage. However, Schwanke et al have already reported a decrease in phagocytosis and oxidative burst performance of standard GC of as much as 50% after 24 h and about 15% after 72 h of storage, underlining the tremendous functional improvement in purified GC after 72 h. 4 We completely agree with Baykara et al that any new medical technology/treatment should finally be judged in practice. Demonstrating that purified GC also provides real benefit to our patients is of enormous importance and should therefore be clinically tested.…”
Section: Granulocyte Products: the Saga Continuessupporting
confidence: 79%
See 3 more Smart Citations
“…Baykara et al argue an absence of any significant differences in the functionality between standard GC and purified GC after more than 24 h of storage. However, Schwanke et al have already reported a decrease in phagocytosis and oxidative burst performance of standard GC of as much as 50% after 24 h and about 15% after 72 h of storage, underlining the tremendous functional improvement in purified GC after 72 h. 4 We completely agree with Baykara et al that any new medical technology/treatment should finally be judged in practice. Demonstrating that purified GC also provides real benefit to our patients is of enormous importance and should therefore be clinically tested.…”
Section: Granulocyte Products: the Saga Continuessupporting
confidence: 79%
“…Some suggest that certain clinical situations require focused emphasis of blood products, such as early platelet and fibrinogen replacement in obstetrical hemorrhage for example, but how often do these sound suggestions based on differing bleeding pathophysiologies make it to bedside protocols and decision support? 3,4 Herein lies the risk; the blood bank protocolizes massive transfusion delivery to rapidly mobilize resources, and then relies on clinicians to resuscitate appropriately, including using protocols and transfusion ratios as clinically indicated. By calling it a protocol, two dangers emerge.…”
Section: Author Contributionsmentioning
confidence: 99%
See 2 more Smart Citations
“…3 Thereafter, transfusion rates declined in both total knee arthroplasty (17.5%-0.92%) and total hip arthroplasty (35.9%-16.9%) between 2011 and 2018. 4 In this regard, a sub-analysis of earlier versus later hip arthroplasty data by Lim et al would have been useful in evaluating whether predictive values of abnormal coagulation tests changed over time in a specialty-specific manner. Restrictive transfusion strategies and antifibrinolytic therapy as part of patient management contributed to the recent transfusion practice changes.…”
mentioning
confidence: 99%